ANALISIS PENGARUH AKTIVITIAS MEDIA SOSIAL TERHADAP NIAT MEMBELI DENGAN MEDIASI CITRA MEREK: Indonesia - steven tay; lily Purwianti (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
The research implemented aims to determine the effect of social media marketing activities with the dimensions of entertainment, interaction, customization, trendiness and ewom on purchase intentions through the mediation of brand image on sports shoes. The research method uses a side technique, namely non-probability sampling which also includes judgmental sampling as a guide that is used in determining the sample. The population used is social media users such as instagram, facebook, tiktok, whatsapp and youtube as well as getting to know the nike, adidas, ardiles, reebok and diadora sports shoes as many as 350 people in which questionnaires are distributed using social media. The tool used to manage data is SmartPLS. Based on the results of the study, it can be concluded that the dimensions of social media activity that have a direct or indirect influence on purchase intention are customization, trendiness and ewom.